Perencanaan Mesin Pembuat Serbuk Jahe - Fernando, Pungki; Risal, Abu; Mukhnizar, Mukhnizar; Afdal, Afdal; Selviyanty, Veny (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The ginger powder making machine is designed and simulated to make it easier to get ginger juice or ginger water for the body to consume. The process of making ginger powder consists of: Power planning for planning a ginger cutting machine Pd = 0.88 kw, Material shaft S30C, diameter ?24 and tensile strength 48 kg/mm2, Bearing type = 6205, two pulleys used, namely drive pulley = 80 mm and the driven pulley = 76.2 mm, the planning speed around the pulley is V = 5.861 m/s. belt length 502.4 mm = 19.77 inches. The shear stress on the 12 mm diameter bolt = 0.188 kg/mm2 and the shear stress on the 14 diameter bolt = 0.141 kg/mm2. The design tangential force on the pin is F = 204 kg and the shear stress on the post plan is ?_k= 2.04 kg/mm2 . Planning Gear box using a ratio of 1: 50, Planning a clutch flans using type FCL 90, Cutting speed of the blade V = 0.48 m/min.